\left[x \right] = \left[ \frac{-1}{4}\right][x]=[4−1] = x*3 +3x*2+6) - (9x*2-5x+7
Answer:
8
Step-by-step explanation:
Step-1 : Multiply the coefficient of the first term by the constant 1 • -16 = -16
Step-2 : Find two factors of -16 whose sum equals the coefficient of the middle term, which is 6 .
-16 + 1 = -15
-8 + 2 = -6
-4 + 4 = 0
-2 + 8 = 6 That's it
Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above, -2 and 8
p2 - 2p + 8p - 16
Step-4 : Add up the first 2 terms, pulling out like factors :
p • (p-2)
Add up the last 2 terms, pulling out common factors :
8 • (p-2)
Step-5 : Add up the four terms of step 4 :
(p+8) • (p-2)
Which is the desired factorization
Answer:
80%
Step-by-step explanation:
28/35=4/5
4/5=0.80
0.80=80%
Answer:
<em> </em><em>the</em><em> </em><em>right</em><em> </em><em>answer</em><em> </em><em>is</em><em> </em><em>1</em><em>2</em><em>*</em><em>3</em><em>=</em><em>3</em><em>6</em>
<em>Hope</em><em> </em><em>this</em><em> </em><em>will</em><em> </em><em>help</em><em> </em><em>u</em><em>.</em><em>.</em><em>.</em>